2007
DOI: 10.1021/bc700306n
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Different IgG1 Antibodies via Glutamine and Lysine using Bacterial and Human Tissue Transglutaminase

Abstract: The modification of proteins by chemical methods is well-established, however usually difficult to control. In this paper, we describe the posttranslational modification of different IgGs via the Lys or Gln side chains catalyzed by bacterial and human tissue transglutaminase (BTGase and TG2). For proof of concept, different IgG1s (commercial bovine IgG1, and L1CAM targeting chCE7 and chCE7 aglycosylated) were enzymatically functionalization with different fluorescent TGase substrates based on the CY3 analogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 21 publications
4
47
0
Order By: Relevance
“…This is not possible to the same degree in the reversed reaction where protein lysines are modified because of the much lower molar solubility of proteins. Although this type of reaction has been reported previously, 23,24 it was an initial concern that the hydrolysis sidereaction would be predominant. This appeared not to be the case.…”
Section: Site-selective Modification Of Hgh 233mentioning
confidence: 87%
“…This is not possible to the same degree in the reversed reaction where protein lysines are modified because of the much lower molar solubility of proteins. Although this type of reaction has been reported previously, 23,24 it was an initial concern that the hydrolysis sidereaction would be predominant. This appeared not to be the case.…”
Section: Site-selective Modification Of Hgh 233mentioning
confidence: 87%
“…Most notably, Schibli and coworkers at ETH Zurich have exploited TGases for chemoenzymatic antibody conjugations [18]. Working primarily with microbial transglutaminase (mTGase), the researchers have found that while antibodies possess many glutamine residues, only aglycosylated or deglycosylated antibodies can be functionalized appreciably using mTGase [19, 20]. The deglycosylation of the antibody at the N297 position increases the flexibility of the peptide backbone, exposing Q295 for reaction with the enzyme.…”
Section: Peptide Tagsmentioning
confidence: 99%
“…4; Fig. 5a) [20]. In subsequent investigations, the laboratory used mTGase to modify variants of chCE7 and rituximab that had been enzymatically deglycosylated with PNGaseF (chCE7degl and RTXdegl).…”
Section: Peptide Tagsmentioning
confidence: 99%
“…The first approaches to enzymatically conjugate biotin and fluorescent dyes to antibodies yielded heterogeneous antibody conjugates with regard to the PAR while the site of conjugation could not be determined [134,135]. It was not until Jeger et al discovered a single glutamine in the human IgG heavy chain domain (Q295), which is next to the antibody glycosylation site (N297), to be the sole site of modification for MTGase-mediated bioconjugation.…”
Section: Transglutaminasesmentioning
confidence: 99%